Treatment of 2-Part Proximal Humeral Fractures in Osteoporotic Patients With Medial Calcar Instability Using a PHILOS Plate Plus an Allogeneic Fibula Inserted Obliquely – A Retrospective Study. (29th September 2021) - Cheng, Huihui; Yu, Jiali; Dong, Zhirui; Lin, Huanyi; Liu, Qilong; Zhang, Xinchao; Wu, Jianguo; Zeng, Xianshang; Yu, Weiguang; Xu, Bo
Introduction: To date, there is little research assessing the efficacy of a proximal humeral internal locking system (PHILOS) plate plus an allogeneic fibula inserted obliquely in the treatment of 2-part proximal humerus fractures (PHFs) with calcar comminution in patients >60 years old with severe osteoporosis. The aim of this study was to retrospectively evaluate the outcomes of elderly patients with osteoporotic 2-part PHFs combined with medial column (calcar) instability or disruption who experienced a PHILOS plate plus an allogeneic fibula inserted obliquely. Materials and Methods: One hundred and twelve consecutive elderly patients with severe osteoporotic 2-part PHFs combined with calcar instability or disruption who were treated with a PHILOS plate plus an allogeneic fibula inserted obliquely were retrospectively identified from 3 tertiary medical centres during 2014–2019. The primary outcomes were the Constant scores and American Shoulder and Elbow Surgeons (ASES) scores; secondary outcome was the rate of key orthopaedic complications. Results: Median follow-up was 24 (15.3–27.6) months. Significant improvements in the median Constant scores were observed (39 [26–58 points] prior to surgery vs 81 [67–95 points] at final follow-up). The median ASES scores improved from 43 (26–64 points) prior to surgery to 83 (65–96 points) at final follow-up. The percentage of key orthopaedic complications was 25.6% (22/86). Four (4.7%) cases had loss of reduction, 4 (4.7%) experienced aseptic loosening, 1 (.8%) had non-union, 4 (4.7%) suffered a periprosthetic fracture, 3 (3.5%) experienced a revision surgery, 1 (.8%) had a dislocation and 5 (5.8%) suffered an unbearable shoulder pain. Conclusion: For elderly patients with osteoporotic 2-part PHFs combined with calcar instability or disruption, PHILOS plate combined with an allogeneic fibula inserted obliquely might have recognisable advantages in decreasing the loss of fixation and preventing medial calcar collapse.